Identifying research priorities for pituitary adenoma surgery: an international Delphi consensus statement - Newall, N; Valetopoulou, A; Khan, DZ; Borg, A; Bouloux, PMG; Bremner, F; Buchfelder, M; Cudlip, S; Dorward, N; Drake, WM; Fernandez-Miranda, JC; Fleseriu, M; et al. (Springer, 2025)
Purpose: Pituitary surgery is the mainstay treatment for most pituitary adenomas, but many questions remain about perioperative and long-term management and outcomes. This study aimed to identify the most pressing research priorities in pituitary surgery with input from patients, caregivers, and healthcare professionals. Methods: An initial survey of patients, caregivers, and healthcare professionals assembled priorities related to preoperative care, surgical techniques, and postoperative management in pituitary surgery. Priorities were thematically grouped into summary priorities, and those answered by existing evidence were omitted following a literature review. An interim survey asked patients, caregivers, and healthcare professionals to select their top 10 priorities from the remaining list. The highest-ranked priorities advanced to a consensus meeting, where the top 10 questions were prioritized. Results: In the initial survey, 147 participants—60.5% of whom were patients, caregivers, or patient support group representatives—submitted 785 priorities, which were then condensed into 52 summary priorities. After a literature review, 33 unanswered priorities were included in the interim survey, completed by 155 respondents, of whom 54.2% were patients, caregivers, or patient support group representatives. The top-ranked priorities were discussed by 14 participants (7 patients and 7 healthcare professionals) during a consensus meeting. The top 10 priorities covered a variety of themes including enhancing diagnosis and management of pituitary adenomas, advancing surgical techniques and technologies, optimizing the prediction of outcomes and complications, and improving patient support and follow-up. Conclusions: The top 10 research priorities in pituitary surgery aim to align researchers and direct funding in order to maximize impact and champion patient representation.